Paget’s disease of breast with an unusual presentation of involvement of overlying skin of breast: a case report - Kumar, Pravin; Jindal, Arpita; Bhalgat, Bhushan; Swain, Phanindra Kumar; Sharma, Raj Govind (International Surgery Journal, 2020)
Paget’s disease of breast is also known as Paget’s disease of the nipple & mammary Paget’s disease, involving the skin of nipple & areola. It is rare type of cancer with tumors inside the same breast which may be either ductal carcinoma in-situ or invasive breast cancer. We report a case with Paget’s disease of breast which is not only involving the nipple-areola complex but also involving surrounding skin of breast.